Aanknopingspunten Between Civil Law and Islamic Law In The Utilization Of Wakf Land For The Interests Of Wakf Land Productivity - Monaya, Nova; Asep Thobibudin Qolyubi (JURNAL ILMIAH LIVING LAW, 2024)
The aim of this research is to find solutions to legal problems or conflicts that have never been resolved between productivity and users of waqf land, namely with new ideas about land obtained from building buildings on waqf land by conducting a comparative study in Saudi Arabia. The method used in writing is the library method, namely research used to collect information and data with the help of various materials available in the library, with data collection techniques by reviewing books, journals, literature, notes, and several reports related to the problem you want. solved. Data were analyzed and presented descriptively. The results of the research, namely Aanknopingspunten between civil law and Islamic law in the use of waqf land for the purposes of waqf land productivity, can provide a solution to the rigidity of waqf land which prohibits it from being sold, gifted or inherited and guaranteed, so that waqf land does not become abandoned land because it has been managed in an appropriate manner. fairness. Keywords : Aanknopingspunten, Islamic Law, Civil Law, Waqf Land